Asuhan Kebidanan Post Partum Fisiologi di Puskesmas Takalala - Nunung Erviany; Ummul Khair; Ummu Kalsum; Syarifah Sahirah; Nur Zalzadillah; Hasnia Hasnia; Hajar Hajar (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The postpartum period is the period after the birth of the placenta and lasts until the uterus regains its pre-pregnancy size known as the postpartum period. The postpartum period is the time after the placenta is born until the reproductive organs recover. That lasted for about six weeks. The aim of this research is to apply physiological post partum midwifery care to Mrs